Peran Audit Investigatif Badan Pemeriksa Keuangan dan Whistleblowing System dalam Penanggulangan Tindak Pidana Korupsi di Indonesia - Eko Syukri Mulyadi; Rachman Hakim (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Corruption in Indonesia has become a systemic and complex issue, posing a threat to economic, social, and political stability. Despite various efforts, including the establishment of the Corruption Eradication Commission and robust law enforcement, Indonesia’s Corruption Perception Index has remained stagnant or declined in recent years. This is primarily due to the inadequacy of conventional audit methods, which struggle to detect complex and hidden corruption schemes. This study examines how the role of investigative audits by the Supreme Audit Agency (BPK) can be optimized through synergy with the Whistleblowing System (WBS) to enhance corruption eradication efforts in Indonesia. Investigative audits, which focus on detecting fraud, are crucial as they can convert audit evidence into legal proof in corruption cases. However, the BPK’s role is often hindered by limited human resources, independence, and weak coordination. Using qualitative research and a literature review, this study analyzes relevant documents, books, scientific journals, and official reports to identify and classify relevant data. The findings indicate that strong synergy between BPK's investigative audits and the WBS is essential. Optimizing these two instruments requires significant reforms, including strengthening whistleblower protection laws, improving inter-agency collaboration, and fostering a robust anti-corruption culture. The study concludes that BPK’s investigative audits are effective in uncovering state losses, but their success depends on follow-up actions and coordination with law enforcement. The WBS can detect corruption early, but its effectiveness is limited by weak whistleblower protection and lack of trust in internal reporting channels.